2016
DOI: 10.1038/srep31826
|View full text |Cite
|
Sign up to set email alerts
|

Filtrating colorectal cancer associated genes by integrated analyses of global DNA methylation and hydroxymethylation in cancer and normal tissue

Abstract: Recently, 5-hydroxymethylcytosine patterning across the tumor genome was considered as a hallmark of cancer development and progression. However, locus-specific difference of hydroxymethylation between colorectal cancer and normal tissue is unknown. In this study, we performed a newly developed method, HMST-seq, to profile 726 aberrant methylated loci and 689 aberrant hydroxymethylated loci synchronously in genome wide of colorectal cancers, majority of which presented higher methylation or lower hydroxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Finally, using thymine-DNA glycosylase (TDG), the carboxyl group from 5formylcytosine and 5-carboxylcytosine are removed to restore unmethylated cytosine pool (Figure 1; Silva et al, 2017;Jayanthi et al, 2018;Zhu et al, 2018). 5-hmC is an intermediate throughout the process (Li et al, 2016).…”
Section: Mechanism Of Dna Hydroxymethylationmentioning
confidence: 99%
“…Finally, using thymine-DNA glycosylase (TDG), the carboxyl group from 5formylcytosine and 5-carboxylcytosine are removed to restore unmethylated cytosine pool (Figure 1; Silva et al, 2017;Jayanthi et al, 2018;Zhu et al, 2018). 5-hmC is an intermediate throughout the process (Li et al, 2016).…”
Section: Mechanism Of Dna Hydroxymethylationmentioning
confidence: 99%
“…As a bridge between the genetic and environmental factors, epigenetic modification plays an important role in cancer initiation and progression. DNA methylation is acknowledged as the principle mechanism of dysfunction of tumor suppressor genes [ 7 ] and the activation of oncogenes [ 8 ]. DNA methylation has been widely studied in GC and CRC [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HBB expression has been found to be inhibited in anaplastic thyroid cancer cell lines/tissues and oral tongue squamous cell carcinoma (Onda et al, ; Suresh et al, ). As a Kunitz serine protease inhibitor, TFPI2 can inhibit many serine proteases, including trypsin, plasmin, plasma kallikrein, and chymotrypsin (Li et al, ). Studies have shown that the low expression of TFPI2 in small cell lung cancer (SCLC) can promote proliferation of the cells (Cao, Guo, Yin, Li, & Zhou, ).…”
Section: Discussionmentioning
confidence: 99%